Praktik Higiene Personal dan Keberadaan Bakteri Escherichia coli Pada Tangan Penjual Petis (Studi di Pasar Anom Kecamatan Sumenep Kabupaten Sumenep) Personal Hygiene Practice and Existence of Escherichia coli Bacteria In Fish Paste Seller’s Hand (Study in - Yuli Rukmi Hasanah; Ellyke Ellyke; Prehatin Trirahayu Ningrum (Pustaka Kesehatan, 2018)
Abstract Personal hygiene practices in food processing must be considered as a potential source of food handlers in the transfer of microorganisms that can cause food contamination. Fish Peste is the commodity from the fish processing which is usually used as a side dish or a typical mix of traditional food. On the other hand, fish paste is a food that is served without reheating and directly without the use of tools such as spoons or plastic gloves so it can be potentially contaminated with bacteria such as Escherichia coli. Research is aimed to identify how the personal hygiene practices and the presence of Escherichia coli bacteria on the hands of the fish paste sellers placed in open containers in Anom Market of Sumenep district of Sumenep regency. The research was descriptive with quantitative approach. The sample uses a total sampling of 15 respondents fish paste seller. The results of this study indicate that the practice of personal hygiene, most of the 12 respondents categorized of adequate personal hagiene practices, among others from contagious diseases, nails and hands hygiene, hair hygiene, clothing hygiene, wash hands thoroughly, and use tools when handling food. From the results of laboratory test, the samples hands of fish paste seller there were 3 respondents were positive presence of Escherichia coli. Keywords: Personal Higyene Practice, Fish Paste, and Escherichia coli Bacteria